2018
DOI: 10.5867/medwave.2018.01.7166
|View full text |Cite
|
Sign up to set email alerts
|

Students’ scientific production: a proposal to encourage it

Abstract: The scientific production of medical students in Latin America, is poor and below their potential. The reason for this is the low theoretical and practical knowledge of scientific writing, a low margin for new knowledge generation, a heavy academic and clinical load, and the expected profile of the medical school graduate. In the present short communication, we propose teaching courses in research methodology, scientific writing in English and Spanish, a personalized search for students and mentors with resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 8 publications
0
17
0
15
Order By: Relevance
“…Personalized counseling is required, being only achievable by having a researcher as a mentor, someone possessing the will and disposition to dedicate a significant amount of time to this customized training. 28 The main limitation of the present study is the impossibility to generalize the reported results, being only applicable to the population studied. However, the…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Personalized counseling is required, being only achievable by having a researcher as a mentor, someone possessing the will and disposition to dedicate a significant amount of time to this customized training. 28 The main limitation of the present study is the impossibility to generalize the reported results, being only applicable to the population studied. However, the…”
Section: Discussionmentioning
confidence: 88%
“…With the purpose of increasing the number of successful writers and authors on health sciences, it would be advisable to implement strategies for training in scientific writing within the undergraduate curriculum of biomedical disciplines, as well as to develop continuous education courses on this subject, aimed at professionals. 27,28 Another influential factor could be bad counseling from teachers, resulting in discouraged students and articles left unpublished. 28,29 The present study suggests that perception of research increases positively with academic progression, differing from what was reported by Alarco et al, 13 and coinciding with Giri et al, 30 A possible explanation would be that current students in the clinical cycle must face increasingly complex situations during their pre-professional internships compared to their colleagues from previous years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomando en cuenta esto, los hallazgos acerca de la publicación científica de tesis son preocupantes. El hecho de que solo tres investigaciones culminaron con la etapa de la difusión de resultados en revistas científicas, corrobora en cierta medida lo mencionado por diversos investigadores respecto a la existencia de limitantes para la producción científica desde el pregrado (Alarco, Changlio-Calle & Cahuana-Salazar, 2017;Corrales-Reyes & Dorta-Contreras, 2018). Esto podría deberse a múltiples causas, pudiendo ser la calidad de las tesis una muy importante, otra podría encajar en el hecho de que los asesores no tienen experiencia en publicación científica, una realidad muy documentada en este país (Mamani et al, 2020).…”
Section: Discussionunclassified
“…La presente investigación permite aproximarse a la realidad de la investigación formativa en salud de las universidades del departamento de Puno, Perú. El hecho de que solo cinco tesis culminaron con la etapa de la difusión de resultados en revistas científicas, corrobora en cierta medida lo mencionado por diversos investigadores respecto a la existencia de limitantes para la producción científica desde el pregrado (11)(12)(13) .…”
Section: Discussionunclassified